Evaluating the effectiveness of educational games: a digital game-based approach to teach programming concepts for kindergarteners - Gomes, Tancicleide C. S.; de Castro, Fernanda C.; Alencar, Andreza (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2017: Anais do XXVIII Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2017.574, 2017)
The development of computational thinking since primary education has been defended over the last few years. In this context, the present work sought to evaluate the effectiveness of educational games through a teaching experience based on digital programming games for children. Finally, these games are evaluated by usability heuristics adapted to educational software. Obtained results indicate the learning of some concepts in a satisfactory way, however few relevant artifacts are pointed out to support the programming teaching in this age group, besides dif􀃔culties in the use experience.